Numerical and experimental simulation of liquefaction for scenario earthquake - Kamatchi, P.; Gayathri, M.; Dilna, M. (Journal of Structural Engineering, 2024)
In this paper, numerical simulation of liquefaction has been done and comparisons are made with the results from experiment on shake table. Properties of river sand sample which are required for numerical simulations are obtained through laboratory tests. Scenario earthquake is artificially generated with seismological parameters of Mw 7.6 Bhuj earthquake January 2001 and numerical simulations are carried out using OpenSeesPL computer program. The excess pore pressure ratios, shear stress-strain histories and stress paths are studied. River sand sample passing through 1.18 mm sieve is filled in Perspex glass box for a dimension of 1.15 m × 1 m × 0.54 m and tested on shake table. A model frame of 7 storey building is placed in the soil specimen and instrumented for the observation of settlement. The time of occurrence of liquefaction observed from numerical simulation is 4.8s and found to be in agreement with the observation from the experiment on shake table. Further, the acceleration response at 110 mm from base observed in the experiment and numerical simulation are compared and are found to be in good agreement. This study, demonstrates the applicability of numerical simulations in prediction of liquefaction phenomenon and dynamic response analysis of typical soil sites for scenario earthquakes.